ROLE OF AYURVEDIC MEDICINAL PLANTS IN CHILDHOOD NEUROPSYCHIATRIC DISORDERS: AN EVIDENCE BASED APPROACH - Kute, *Arun Parmeshwar; Kumari Ojha, Nisha; Kumar, Abhimanyu (International Journal of Ayurveda and Pharma Research, 2018)
The concept of mental health has been dealt in Ayurveda with great emphasis. In our classical texts, the equilibrium of Satva-Raja-Tama is considered as foundation for perfect health status. The principles of Ayurveda still hold very true in managing childhood neuropsychiatric disorders. Medhya drugs has been used since antiquity for the effective management of the disorders. But in this era of scientific aptitude, it is the need of hour to practice evidence based medicine by the use of various Medhya drugs described in Ayurvedic texts for the management of neuropsychiatric disorders. Medhya herbs provide special nourishment to neuronal tissue and are thus used to enhance memory, cognition, and help in coping various neuropsychiatric problems. In this context, the present paper will focus on scientific exploration of Medhya dravyas like Brahmi (Bacopa monneri), Mandukparni (Centella asiatica), Shankhpushpi (Convolvulus pleuricaulis), Jatamansi (Nordostachys jatamansi) and Vacha (Acorus calamus) to validate the ancient views regarding effective management of neuropsychiatric disorder.